Genetic studies of normal tension glaucoma - D.Yu. Plotnikov; E.V. Valeeva (РМЖ "Клиническая офтальмология")
D.Yu. Plotnikov, E.V. Valeeva Kazan State Medical University, Kazan, Russian Federation The paper presents a review of literature on genetic studies of normal tension glaucoma (NTG). Actually, it is known that NTG is a multifactorial disease whose development includes environmental and genetic factors. To date, a number of studies focused on NTG-associated genetic factors was performed. Several of them reported that polymorphisms of the OPA1 and OPTN genes can be genetic markers of NTG risk. The studies demonstrated that polymorphisms of genes encoding mitochondrial proteins including mitofusins 1 and 2, as well as the PARL gene, are associated with an increased NTG risk. In addition, an association of single-nucleotide polymorphisms of the Toll-like receptor 4 gene with NTG was revealed. Altered immune response and enhanced apoptosis may also play a role in NTG pathogenesis. Variations in a number of TBK1 gene copies are also associated with NTG development in some populations. Among multiple genome-wide association studies (GWAS) of the glaucoma, genetic architecture of NTG has been studied only in isolated cases. These studies identified several NTG-associated genes such as SRBD1, ELOVL5, CDKN2B-AS1, FOXC1, TMCO1, CDKN1A and SIX1-SIX6. The genetic study results provide a better understanding of the glaucoma development mechanisms, and the data can be used to design novel diagnostic and therapeutic methods. Keywords: glaucoma, normal tension glaucoma, genes, genetic studies, polymorphisms. For citation: Plotnikov D.Yu., Valeeva E.V. Genetic studies of normal tension glaucoma. Russian Journal of Clinical Ophthalmology. 2024;24(4):193–199 (in Russ.). DOI: 10.32364/2311-7729-2024-24-4-5